Open Access to E-journals in Library and Information Science - Rajput, Prabhat Singh; Naidu, G. H. S. (Journal of Information and Knowledge, 2013)
E-Journals are now a reality in the age of information technology. With the advent of Internet, users can access many e-journals, magazines and newsletters any time from anywhere for their academic and research development in open access. Explains the benefits of e-journals and provide full bibliographical description of open access e-journals in the area of Library and Information Science.